Atopic dermatitis, STAT3‐ and DOCK8‐hyper‐IgE syndromes differ in IgE‐based sensitization pattern. Issue 7 (July 2014) - Boos, A. C.; Hagl, B.; Schlesinger, A.; Halm, B. E.; Ballenberger, N.; Pinarci, M.; Heinz, V.; Kreilinger, D.; Spielberger, B. D.; Schimke‐Marques, L. F.; Sawalle‐Belohradsky, J.; Belohradsky, B. H.; et al.
Abstract Background Increased serum IgE levels are characteristic but not specific for allergic diseases. Particularly, severe atopic dermatitis (AD) overlaps with hyper‐IgE syndromes (HIES) regarding eczema, eosinophilia, and increased serum IgE levels. HIES are primary immunodeficiencies due to monogenetic defects such as in the genes DOCK8 and STAT3. As it is not known to date why allergic manifestations are not present in all HIES entities, we assessed the specificity of serum IgE of AD and HIES patients in the context of clinical and immunological findings. Methods Clinical data, skin prick tests, specific IgE to aero‐ and food allergens, and T helper (Th) subpopulations were compared in AD and molecularly defined HIES patients. Results Total serum IgE levels were similarly increased in STAT3‐HIES, DOCK8‐HIES, and AD patients. The ratio of aeroallergen‐specific IgE to total IgE was highest in AD, whereas DOCK8‐HIES patients showed the highest specific serum IgE against food allergens. Overall, clinical allergy and skin prick test results complied with the specific IgE results. Th2‐cell numbers were significantly increased in DOCK8‐HIES and AD patients compared to STAT3‐HIES patients and controls. AD patients showed significantly higher nTreg‐cell counts compared to STAT3‐HIES and control individuals. High Th17‐cell counts were associated with asthma. Specific IgE values, skin prick test, and T‐cell subsets of STAT3‐HIES patients were comparable with those of healthy individuals except decreased Th17‐cell counts. Conclusion Hyper‐IgE syndromes and atopic dermatitis patients showed different sensitization pattern of serum IgE corresponding to the allergic disease manifestations and Th‐cell subset data, suggesting a key role of DOCK8 in the development of food allergy.